Modelo de gestión del conocimiento para pymes, basado en el sistema de gestión de la calidad y la gestión documental (2020)
Some studies show that the knowledge that organizations need to improve their performance can be managed more effectively when articulated with quality management and document management. A model for knowledge management was developed applying a qualitative method, based on a literature review and the identification of document management practices in selected SMEs, that integrates knowledge management with the quality management system and with document management, according to the technical standards NTC ISO 9001:2015 and NTC ISO 33001:2011 respectively. This model integrates knowledge captured from outside with that created in the organization, in order to facilitate its management under the limited conditions of SMEs.